PREVALENCE OF ENTEROCOCCUS FAECALIS AND E. FAECIUM INLIVE PANGASIANODON HYPOPHTHALMUS OBTAINED FROM RETAIL FISH MARKETS IN LUCKNOW, INDIA AND THEIR ANTIMICROBIALRESISTANCE PROFILE - KUMAR, ANIL; DWIVEDI, DR. ARTI; SONI, MAYANK; SAHU, VIKASH; IMRAN, MOHD; KUMAR, CHANDRA BHUSHAN; SARKAR, U. K.; RATHORE, GAURAV (Journal of the Inland Fisheries Society of India, 2024)
Enterococcus faecalis and E. faecium can cause severe infections in human and their presence in food, especially when multidrug-resistant, threatens human health. This study documented the prevalence of E. faecalis and E. faecium in Pangasianodon hypophthalmus collected from retail fish markets in Lucknow, Uttar Pradesh and determined their antimicrobial resistance (AMR). The prevalence of E. faecalis was 47.05% and 35.29% for E. faecium. Both the enterococcal species showed higher resistance to erythromycin ( 76%) and lower resistance (<30%) to tetracycline, quinopristion-dalfopristion, ciprofloxacin and chloramphenicol. Multidrug resistance was higher in E. faecium as compared to E. faecalis. Our study highlights AMR profile of enterococcal isolates from pangasius and suggests the need of improving hygiene in the fish markets.